Role of 68Ga-DOTA-TOC PET/CT in the Evaluation of Meningiomas with Osseous Involvement - Sharjeel Usmani; Syed Furqan Hashmi; Anjali Jain; Khulood Al Riyami; Rashid al Sukaiti; Najeeb Ahmed; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2026)
Meningiomas with osseous involvement present unique diagnostic and therapeutic challenges due to their variable patterns of bone remodelling, hyperostosis, and direct bone infiltration. While MRI and CT remain the standard imaging modalities for evaluating soft-tissue extension and bony architecture respectively, they often fall short in accurately distinguishing true tumour invasion from reactive changes, particularly in complex skull-base and calvarial locations. 68Ga-DOTA-TOC PET/CT represents a pivotal advancement in the imaging of meningiomas with osseous involvement, enhancing diagnostic accuracy, enabling multimodality management, and supporting personalized therapeutic strategies. Keywords: 68Ga-DOTA PET/CT; meningiomas; radiotherapy planning